Real-time Imaging of the Electric Conductivity Distribution inside a Rechargeable Battery Cell - MATSUDA, Seiju; SUZUKI, Shogo; YABUMOTO, Kai; OKADA, Hideaki; MIMA, Yuki; KIMURA, Noriaki; KIMURA, Kenjiro (Denki kagaku oyobi kōgyō butsuri kagaku, 2021)
The aim of this study is to observe the spatial inhomogeneity of a rechargeable battery’s electric conductivity distribution. Therefore, we have developed a system that uses the measurement results of a minute magnetic field that leaks from the cell to visualize, in real time, the cell’s electric conductivity distribution. This system has a magnetic detection capability of 30 pT/Hz0.5 (at 1 Hz); it measures the magnetic field distribution in the 240 × 240-mm range. This system has the ability to detect the 500-µA electric current that flows in a rechargeable battery 5 mm away from the sensor module. Because the magnetic signals are detected at the frequency synchronized with the alternating current flowing in the cell, this system is not affected by environmental magnetic field noise. Using this system, we have successfully visualized the short-circuit spot in a cell with significant self-discharge. Furthermore, we observe that the magnetic field distribution changes continually when the short circuit is being generated. The coordinate where the magnetic field distribution changed and the coordinate where metal precipitates were confirmed significant agreement.